BIM Methodology and Montecarlo Analysis as Mitigation Tools of Construction Cost Overrun - Meza, Gonzalo (2025)
Construction project management frequently encounters significant cost control challenges, with cost overruns being among the most persistent and critical issues. This paper proposes a risk management method for multifamily housing projects that integrates BIM methodology with Monte Carlo analysis. This combination enables a detailed visual and quantitative assessment, facilitating risk identification and quantification, and providing precise cost control. Through comprehensive analysis, including literature reviews, case studies, and surveys of construction experts-the primary risk factors contributing to cost overruns were identified, such as design errors and cost estimation issues. Results indicate that the combined use of BIM and Monte Carlo enhances resource planning and minimizes cost overruns. Validation surveys demonstrate considerable acceptance of this method among professionals, who recognize its effectiveness and applicability in risk management for multifamily projects.